Динаміка змін у системі міських пасажирських перевезень - Біліченко, Віктор; Цимбал, Сергій; Біліченко, Наталія (Посвіт, 2019)
The system of passenger transportation of the city of Vinnitsa to the introduction of a new network, after its introduction and at the moment, is described. Proposed ways to further improve the city's passenger transportation system.
Dynamics of the change in the passenger transportation system
Keywords: 656.13.072